Mechanical performance analysis of an asphalt mixture modified with bamboo fiber - Jiménez, Angie (2025)
International organizations such as the UN recognize the importance of acting against climate change. For this reason, several countries such as Costa Rica, plan to achieve carbon neutrality in the coming years. As a result, the use of biodegradable materials in different applications has increased. In this regard, this article presents a sustainable alternative to asphalt mixture additives: the use of bamboo fibres. Therefore, one of the objectives of this research is to promote the use of bamboo, which holds multiple benefits to the environment such as: carbon fixation, avoids soil erosion, generates job opportunities related to cultivation, among others. It is worth mentioning that the culm fibres are used in this research as a final product and not as a waste, this way the plant grows again after harvesting, generating a sustainable cycle. This research presents the analysis and mechanical performance of an asphalt mixture modified with bamboo fibres of the guadua angustifolia species. The main objective was to evaluate its mechanical behavior of the resulting mixture by means of the SUPERPAVE methodology. As a result, an improvement in the resistance of the mixture to fatigue and moisture damage was obtained, which is promising and opens a possibility to the use of fibres in these materials.